Hermeneutical Study of Surah al-Baqarah Verse 177 "Al-Birru Wa at-Taqwa" in the Book of Anwar At-Tanzil Wa Asrar At-Ta'wil - Hilyati Aulia - (AQWAL Journal of Qur'an and Hadis Studies, 2020)
The process of understanding is a natural process that will be experienced by all human beings. Including the mufassir can not be separated from the activity of understanding. In the study of the Koran, active understanding activities are carried out, including Imam al-Baidawi. Anwar At-Tanzil Wa Asrar At-Ta'wil is a book that has received a lot of praise and criticism from scholars. This paper is intended to find out the hermeneutical thoughts of Imam al-Baidawi and his interpretation related to surah al-Baqarah verse 177 because at first glance the public sees this verse as a postulate for moving the Qibla from the Aqsa Mosque to Mecca, namely the direction of the Kaaba. This article is a qualitative type of article with a Schleiermacher hermeneutic approach. The subject of this article is the hermeneutical thinking of Imam al-Baidawi and sura al-Baqarah verse 177. The research results of this article are hermeneutical thinking in the art of understanding Imam al-Baidawi with a subjective view by using grammatical interpretation and prejudice of the mufassir based on his experience and al-birr in Surah al-Baqarah verse 177 means obeying all God's commands is a virtue which then gives birth to muttaqun indicators.